Model persamaan struktur kesetiaan pelanggan perkhidmatan jalur lebar HSDPA - Nur Riza Mohd Suradi,; Zalina Mohd Ali,; Zainol Mustafa,; Faridatulazna Ahmad Shahabuddin,; Wan Rosmanira Ismail,; Rofizah Mohamad, (Penerbit ukm, 2009)

(untitled)
This paper reports the structural equation modelling of the interrelationship among several latent factors which include customer satisfaction and customer loyalty for describing the quality of broadband wireless service HSDPA. A survey was conducted using questionnaires filled by 385 customers of HSDPA obtained through e-mails and internet discussion forum. The study found that network performance in terms of speed, connectivity, mobility and access affected customer satisfaction positively and significantly, while customer satisfaction influenced customer loyalty